EXPLORING THE IMPACT OF SERVICE QUALITY ON TOURIST SATISFACTION AND LOYALTY IN TRADITIONAL FOOD EXPERIENCES: A STUDY OF UTTARAKHAND’S CULINARY TOURISM - Arya, Virendra Kumar; Singh, Akhilesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Food tourism has gained prominence as travelers increasingly seek authentic culinary experiences that reflect the heritage and traditions of a destination. Despite its rich cultural and gastronomic heritage, Uttarakhand’s traditional cuisine remains underutilized in tourism promotion. This study explores the impact of service quality on tourist satisfaction and loyalty in Uttarakhand’s traditional food experiences. Using the SERVQUAL model, the study evaluates five key service quality dimensions: Tangibility, Reliability, Responsiveness, Assurance, and Empathy, to assess their influence on tourists’ perceptions and overall satisfaction with food tourism in the region. Data was collected from 301 respondents visiting Mussoorrie and Rishikesh (Garhwal region) and Nainital and Mukteshwar (Kumaon region) using a 5-point Likert scale survey. The study employed Exploratory Factor Analysis (EFA) and Structural Equation Modeling (SEM) to analyze the relationships between service quality factors and tourist satisfaction. The results indicate that all five dimensions significantly influence tourist satisfaction, with Reliability (β = 0.378, p < 0.001) emerging as the strongest predictor, followed by Tangibility (β = 0.312, p < 0.001), Responsiveness (β = 0.295, p < 0.001), Empathy (β = 0.282, p < 0.001), and Assurance (β = 0.265, p < 0.002). The findings reinforce that maintaining high standards of hygiene, food presentation, service consistency, and cultural storytelling significantly enhances tourist satisfaction and destination loyalty. The study contributes to food tourism literature by applying the SERVQUAL model to a regional cuisine setting and highlights key policy recommendations for integrating food tourism into Uttarakhand’s broader tourism strategy. Future research can explore the role of digital innovations, food safety regulations, and cross-cultural preferences to further improve food tourism experiences. By addressing these areas, Uttarakhand can strengthen its culinary tourism offerings and position itself as a top food tourism destination in India.